Bridging distance: Practical and pedagogical implications of virtual Makerspaces. (19th June 2020) - Lock, Jennifer; Redmond, Petrea; Orwin, Lindy; Powell, Alwyn; Becker, Sandra; Hollohan, Paula; Johnson, Carol
Abstract: Makerspaces are locations where people with common interests can work on projects, share ideas, tools and expertise to make or create. There is an abundance of "how to" guides and research studies on physical makerspaces, little research focuses on describing the virtual making processes and the experiences therein. This qualitative study explores the experiences of seven participants who engaged in a synchronous virtual makerspace. Meeting once a month over 16 weeks, members of the International Maker Educator Network participated in the making of a robot. This case study describes how the virtual making occurred, the personal experiences of the makers, technology used to support virtual making, and the affordances and inhibitors of virtual making. Data are analysed through the lens of a professional learning community and the People, Means and Activities makerspace framework. The paper concludes with implications for virtual making in practice and future research opportunities. Lay Description: Makerspaces are locations where people with common interests can work on projects, share ideas, tools and expertise to make or create. Little is known about virtual making in formal or informal makerspaces. Participants had positive perceptions of their online virtual making experiences. Affordances of virtual makerspaces Inhibitors of virtual makerspaces Considerations must be made for scaling up and sustainability. Effective design and facilitation of authentic learning for virtual making is key. Access and use of technology affords virtual making across geographical boundaries.